Inventory of erosional features related to the residual CO 2 -ice-cap of the south polar region on Mars - Preuschmann, S.; van Gasselt, S.; Reiss, D.; Neukum, G. (2004)
On the residual south polar CO2 cap of Mars a variety of peculiar morphologic features have been observed and attributed to erosional processes mainly. These features include the (1) swiss-cheese-terrain, defined by a variety of almost circular depressions and isolated irregularly shaped mesas with surrounding moats and (2) the fingerprint terrain, which is characterized by large plains with equally-spaced sinusoidal narrow ridges with a length of several kilometers. In this work, both the elongated features and the circular depressions have been mapped between the 80°S-90°S latitude range on the basis of the available imagery of the Mars Orbiter Camera (aerobraking to relay phase), classified by their small-scale morphology and put in a seasonal context. As far as possible, morphometry measurements have been performed on the basis of topographic data of the Mars Orbiter Laser Altimeter. Beside seasonal variations, observed in earlier work, we have found an abundance of transitional morphologies between the two landforms described above. The lateral distribution of the surface features will be presented with a main attention on seasonal changes. Formation processes have not been fully understood yet but sublimation of CO2-ice near the (sub-)surface has been discussed as a primary process. In this work, additional explanations including eolian processes have been discussed in more detail and the interaction between CO2 deposition, material removal by deflation or sublimation and the development of the characteristic pattern has been included in the analyses regarding the morphogenesis of these landforms.